Advantages of modified osteosynthesis in treatment of osteoporotic long bones fractures : experimental model - Šišljagić, Vladimir (Array, 2009)
Summary: In surgery of fractured long bones, a patient suffering from osteoporosis represents constant challenge to a surgeon and applied material and instruments that need to destroy as little as possible of an already damaged bone. One potential way of increasing the contact surface between the implants and osteoporotic bone is injection of bone cement (methyl-metacrilat, Palakos) into a prepared screw bed. This method of osteosynthesis was therefore subjected to experimental research to prove that application of modified osteosynthesis using bone cement in treatment of fractures in osteoporotic patients has advantage over the standard method of osteosynthesis because this modified method enables significantly greater firmness and stability of the osteosynthesis, which is the essential precondition of a successful fracture healing. The research was carried out on six macerated cadaveric preparations of a shin bone from the osteological collection from Institute for Anatomy, School of Medicine, University »J. J. Strossmayer«. All samples of long bones were artificially broken in the middle part of the diaphysis and then standard osteosynthesis and modified osteosynthesis with screws filled with bone cement were performed on the samples. Results show that under identical static action of the moment of torsion in the modified osteosynthesis torsion angle deviation is lower than in the standard osteosynthesis. In modified osteosynthesis with bone cement the first results for angle of torsion deviation greater than 0.2 degrees were noticed after 120 minutes, while in the standard method of osteosynthesis they were noticed already in the first minute